Evaluation of long-term use of precision agriculture techniques in permanent pastures in Alentejo - Serrano, João M. (2013)
This work evaluates the results of implementing precision agriculture technologies in dry land permanent pastures in the southern region of Portugal over a six year period. A project provided the means for the acquisition of precision farming technologies and demonstration of their potential and limitations in experiments carried out on a 6 ha field with a biodiverse pasture. The technologies sought, on the one hand, to simplify the time-consuming and expensive process of evaluating the soil characteristics and productivity of the pasture and on the other, to optimize the application of fertilizers, the main practice used by farmers to improve pastures. The use of a "DUALEM 1S" electromagnetic induction sensor in association with a GPS receiver allowed the identification of areas in the plot with different potentials and production capacities. The use of a "GRASSMASTER II" probe associated with a GPS receiver, after calibration, proved to be a very interesting tool in non-destructive and rapid assessment of pasture productivity. Through the combination of "FIELDSTAR" and "FERTICONTROL" systems it was possible to control a "VICON RS-EDW" centrifugal fertilizer distributor equipped with variable rate technology (VRT). Closing the cycle in precision agriculture with differentiated application of phosphate fertilizers is an important step in rationalizing the use of economic resources and environmental protection.